RECENT (AND FUTURE) DEVELOPMENTS OF EU COMPETITION LAW: MATTERS OF POLICY AND OF MEMBER STATES COOPERATION (EU and comparative law issues and challenges series (ECLIC), 2020)
EU Competition law has recently incurred main procedural reforms. Their basis must be found in Regulation 1/2003, decentralizing the control on the application of Articles 101 and 102 TFEU, thus emphasising the role of National Competition Authorities and Courts. This system has proved to be far from complete and perfect, as the first part of this article aims at demonstrating. A new political wave has enabled to strengthen the enforcement of EU Competition Law under two strands: the private and the public enforcement. Directive 2014/104 harmonises parts of the national (civil) procedural law regarding damages actions. Powers and duties of National Courts are its focus. Its main features are recalled within this contribution. The long-awaited Directive 2019/1 aims at further reinforcing the role of NCAs, establishing a very detailed piece of legislation, whose main elements are briefly examined here. Since the two acts have been adopted in a quite short period of time, their coordination is analysed too. This exam can lead us to offer some remarks on the perspective role of EU Competition Law, both from the Member States perspective and the needs for reform, and the new Commission’s approach to the consistent application of the new legislation.